Transcriptome analysis of divergent residual feed intake phenotypes in the M. longissimus thoracis et lumborum of Wannan Yellow rabbits - Huang, Dongwei; Wang, Yuanlang; Qi, Pingping; Ding, Haisheng; Zhao, Huiling (Frontiers in Genetics, 2023)
Introduction: Feed efficiency is an important economic trait in rabbit meat production. The identification of molecular mechanisms and candidate genes for feed efficiency may improve the economic and environmental benefits of the rabbit meat industry. As an alternative to the conventional feed conversion ratio, residual feed intake (RFI) can be used as an accurate indicator of feed efficiency. Methods: RNA sequencing was used to identify the differentially expressed genes (DEGs) in the M. longissimus thoracis et lumborum of eight Wannan Yellow rabbits with excessively high or low RFIs (HRFI or LRFI, respectively). Thereafter, Gene Ontology (GO) analysis, enrichment using the Kyoto Encyclopedia of Genes and Genomes (KEGG) database, gene set enrichment analysis (GSEA), and protein-protein interaction (PPI) network analysis was conducted.Results: In total, 445 DEGs were identified in the M. longissimus thoracis et lumborum of rabbits with high and low RFIs. The significantly enriched GO terms identified in these two groups were primarily involved in energy and mitochondrial metabolism and oxidation-reduction processes. KEGG analysis identified 11 significantly enriched pathways, including oxidative phosphorylation, PI3K-Akt signaling, and extracellular matrix-receptor interaction pathways. According to GSEA, the expressions of genes and pathways related to mitochondrial function were upregulated in HRFI rabbits, whereas genes with upregulated expressions in LRFI rabbits were related to immune response and energy metabolism. Additionally, PPI network analysis revealed five potential candidate genetic markers.Conclusion: Comparative analysis of the M. longissimus thoracis et lumborum transcriptomes in HRFI and LRFI rabbits revealed FOS, MYC, PRKACB, ITGA2, and FN1 as potential candidate genes that affect feed efficiency in rabbits. In addition, key signaling pathways involved in oxidative phosphorylation and PI3K-Akt and ECM-receptor interaction signaling impact rabbit feed efficiency.